Social and economic evolution of the ancient Thracians in Homeric, archaic and classical times. (Up to the conquest of Bulgarian lands by the ancient Macedonians)
Recueil: Etudes historiques à l'occasion du XIe Congrès international des sciences historiques, Stockholm-août 1960, p. 1-29.